Karakteristik Ne Bis In Idem dan Unsurnya dalam Hukum Acara Mahkamah Konstitusi - Ilhamdi Putra; Khairul Fahmi (The Constitutional Court of the Republic of Indonesia, 2021)
Ne bis in idem principle in Mahkamah Konstitusi procedural law (Constitutional Court– CC) found in Article 60 Paragraph (1) of CC Act, in prohibition form to return to trial norms previously reviewed. Discrete from Criminal Code and Civil Code which exact ne bis in idem elements, Article 60 Paragraph (1) has sole element within object review form. This research examines two problems: what are ne bis in idem principle characteristics, and what are the elements in the CC procedural law? The normative judicial research method used to understand ne bis in idem principle elative. Ne bis in idem adaptation in CC procedural law resulted broad philosophical shifts that unaffected Petitioners' legal standing and legality of the object that could bring against them. Based on decision systematics, CC put arguments ne bis in idem at Conclusion, so that it is not a verdict. Meanwhile, ne bis in idem principle in CC procedural law carry several norms, however CC Act only has two elements in legal object and legal subject-relationship forms. Meanwhile, the third element in legal development form is found in the CC decision. Because the legal standing of the Petitioners' and the legality of the object that can be challenged was not disturbed, the three elements did not apply accumulatively, in which the element of legal development was more determinant than the other two elements. As result, constitutionality actualization either occurs through positive decisions granted Petitioners' petition, moreover occurred in cases deemed ne bis in idem.